2010
DOI: 10.1161/circresaha.110.227744
|View full text |Cite
|
Sign up to set email alerts
|

In the RyR2 R4496C Mouse Model of CPVT, β-Adrenergic Stimulation Induces Ca Waves by Increasing SR Ca Content and Not by Decreasing the Threshold for Ca Waves

Abstract: Conclusions:In the R4496C CPVT model, the RyR is leaky, and this lowers both SR Ca content and the threshold for waves. ␤-Adrenergic stimulation produces Ca waves by increasing SR Ca content and not by lowering threshold.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
77
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(87 citation statements)
references
References 52 publications
10
77
0
Order By: Relevance
“…Experimentally, electrophysiological mechanisms of arrhythmogenesis in CPVT have been well elucidated over the past several years (2,3,10,12,16,22). Relevant to our modeling study, Cerrone et al (2) showed that RyR2…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Experimentally, electrophysiological mechanisms of arrhythmogenesis in CPVT have been well elucidated over the past several years (2,3,10,12,16,22). Relevant to our modeling study, Cerrone et al (2) showed that RyR2…”
Section: Discussionsupporting
confidence: 61%
“…Using the technique of optical imaging, Fernandez-Velasco et al (10) showed an increase in Ca 2ϩ sensitivity of RyR2 along with a lowered SOICR threshold in the cardiac myocyte isolated from the RyR2 R4496Cϩ/Ϫ knock-in mouse. Similarly, Kashimura et al (16) confirmed that the RyR2 R4496Cϩ/Ϫ cell had lower SR Ca 2ϩ content and a lower SOICR threshold compared with the RyR2wt counterpart and that BAS-induced increase in SR Ca 2ϩ was sufficient to attain the SOICR threshold resulting in the production of Ca 2ϩ waves in the RyR2 R4496Cϩ/Ϫ but not in the RyR2wt cell. Results of our study are in agreement with observations made in these experimental studies.…”
Section: Discussionmentioning
confidence: 81%
“…Both fast pacing and β-adrenergic stimulation, which potentiates both LCC and the SR Ca 2+ -ATPase (SERCA), tend to increase SR load. Increased SR load together with RyR hyperactivity can then jointly promote the initiation and propagation of intracellular Ca 2+ waves that are the hallmark of SCR (18,19). Beyond this pictorial level, TA remains poorly understood.…”
mentioning
confidence: 99%
“…1) [22,46], it seems likely that SERCA activity is reduced to a degree that the resulting slowing of the Ca 2+ uptake into the SR is fully compensated for by Ca 2+ transport via the Na + -Ca 2+ exchanger. Taken together, the data currently available indicate that the reduction in SR Ca 2+ load is predominantly a consequence of a moderately decreased SERCA activity, possibly mediated by reduced PLB phosphorylation and potentially in combination with a reduced set point of SR Ca 2+ content [24] or an increased nonspark diastolic Ca 2+ release [39]. (Fig.…”
Section: Discussionmentioning
confidence: 85%